Layer Height, Temperature Nozzle, Infill Geometry and Printing Speed Effect on Accuracy 3D Printing PETG - Amirur Ridho Muhammad; Rahma Rei Sakura; Dedi Dwilaksana; Sumarji; Muhammad Trifiananto (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2022)
The manufacturing industry has grown rapidly in the last few decades. 3D printing is one of the technologies of manufacturing, this technology makes products by adding filaments that are stacked systematically to become a finished product. PETG filament is a polymer with the name polyester but with glycol modification. This study aims to determine and understand the effect of the process parameters layer height, nozzle temperature, infill geometry and printing speed. This research method uses the Taguchi method with L16 and various parameters; layer height 0.12mm; 0.16mm; 0.2mm; 0.28mm, infill geometry cross; cubic; tri-hexagonal; triangles, nozzle temperature 220ºC; 230ºC; 240ºC; 250ºC and printing speed 40mm/s; 50mm/s; 60mm/s; 70mm/s. After testing, it can be concluded that the most influential parameters are sequentially; layer height, nozzle temperature, printing speed, and infill geometry with layer height parameters have the dominant influence, nozzle temperature and printing speed parameters have a balanced influence and infill geometry parameters have the least influence.